2017
DOI: 10.3389/fpsyg.2017.01862
|View full text |Cite
|
Sign up to set email alerts
|

Huggable Communication Medium Maintains Level of Trust during Conversation Game

Abstract: There have been several attempts in recent years to develop a remote communication device using sensory modalities other than speech that would induce a user’s positive experience with his/her conversation partner. Specifically, Hugvie is a human-shaped pillow as well as a remote communication device enabling users to combine a hugging experience with telecommunication to improve the quality of remote communication. The present research is based on the hypothesis that using Hugvie maintains users’ level of tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…For this purpose, they designed a negotiation task using a telepresence robot [122]. Lastly, Nakanishi et al demonstrated by conducting multiple studies that conversations through a physically huggable humanoid cushion device, called Hugvie [123], enhanced interest and maintained trust in the partner [124,125], reduced negative imagination about a topic [126], and improved attention and memory retention [127] when reading to children.…”
Section: Social Touch Technologiesmentioning
confidence: 99%
“…For this purpose, they designed a negotiation task using a telepresence robot [122]. Lastly, Nakanishi et al demonstrated by conducting multiple studies that conversations through a physically huggable humanoid cushion device, called Hugvie [123], enhanced interest and maintained trust in the partner [124,125], reduced negative imagination about a topic [126], and improved attention and memory retention [127] when reading to children.…”
Section: Social Touch Technologiesmentioning
confidence: 99%
“…Gillespie et al,(2016) used transcripts of the Werewolf game as the evaluation data of their semantic classifier. Takahashi et al,(2017) measured trust between players through the arranged Werewolf game. Wang et al,(2018) built a robot that had abilities such as casting a glance to play the real world Werewolf game.…”
Section: Related Workmentioning
confidence: 99%
“…Over time, the function and meaning associated with the transitional object developed and deepened to provide both safe haven and secure base functions, that is, facilitate soothing but also stimulating the courage to begin to explore. The above example demonstrates how transitional object usage can draw on and integrate ideas from attachment theory (Bowlby, 1988; Feeney & Collins, 2015; Mikulincer & Shaver, 2007), social thermoregulation theory (IJzerman et al ., 2015; Ijzerman, Heine, Nagel, & Pronk, 2017), social touch (Maratos et al ., 2017; Morrison, 2016; Uvnäs‐Moberg, Handlin, & Petersson, 2015), and huggable communication mediums (Nakanishi, Sumioka, & Ishiguro, 2016; Takahashi et al ., 2017). Furthermore, this links back to Harlow’s (1958) work with infant monkeys in discovering the importance of soft tactile sensations accompanied by (physical) warmth in imparting the emotional security (i.e., safeness) to explore (Harlow & Suomi, 1970).…”
Section: Introductionmentioning
confidence: 99%